2018
DOI: 10.1007/s40264-018-0683-x
|View full text |Cite
|
Sign up to set email alerts
|

Cohort Study of Psychiatric Adverse Events Following Exposure to Levonorgestrel-Containing Intrauterine Devices in UK General Practice

Abstract: Statistically significant associations of levonorgestrel exposure with anxiety and sleep problems were observed. Substantive differences in baseline characteristics of the treated groups make robust conclusions difficult but the results strongly suggest that additional studies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 11 publications
3
12
0
Order By: Relevance
“…As previously reported, we found a weak association of LNG exposure with anxiety. This finding is in line with results of an UK cohort study of new IUDs users (HR: 1.18, 95%CI 1.08; 1.29, [21]). Our study used however a more robust statistical method.…”
Section: Discussionsupporting
confidence: 90%
“…As previously reported, we found a weak association of LNG exposure with anxiety. This finding is in line with results of an UK cohort study of new IUDs users (HR: 1.18, 95%CI 1.08; 1.29, [21]). Our study used however a more robust statistical method.…”
Section: Discussionsupporting
confidence: 90%
“…Almost all these events are described in the SPC. Moreover, the anxio‐depressive safety signal was found in a population‐based cohort study of the safety of the Mirena levonorgestrel IUD compared to copper IUDs and with another recent observational study …”
Section: Discussionmentioning
confidence: 67%
“…Moreover, the anxio-depressive safety signal was found in a population-based cohort study of the safety of the Mirena levonorgestrel IUD compared to copper IUDs and with another recent observational study. 20,21 The media coverage peak highlighted and broadcasted information about AEs of Mirena, informing the users that their symptoms could be related to potential AEs of their levonorgestrel-releasing IUD they were unaware of. Indeed, many consumers reported long-standing symptoms, such as depression, weight gain, abdominal pain or breast tenderness, which they had not attributed previously to their levonorgestrel-releasing IUD.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with these findings, a recent Danish national register study reviewed the records of over one million women and observed that the use of LNG-IUS was associated with subsequent antidepressant use and first diagnosis of depression (4). In addition, a cohort study investigating psychiatric ADRs associated with LNG-IUS in the UK general practice, found significant associations between levonorgestrel exposure and records of anxiety and sleep disturbances (6).…”
Section: Discussionmentioning
confidence: 84%
“…Due to the localized release of the drug, blood serum levels of levonorgestrel are lower compared to other hormonal contraceptives, and ADRs were supposed to occur less pronounced or mainly in the initial months of use. However, an increased risk of breast cancer ( 2 ) and an emerging evidence regarding mood disorders and suicide attempts ( 3 6 ) arises the question of clinically relevant systemic and in particular psychotropic effects of LNG-IUS. Previous studies investigated ADRs only over a time period of 3 to 5 years after implantation ( 7 9 ).…”
Section: Introductionmentioning
confidence: 99%